Mortality, complications and failure to rescue after surgery for esophageal, gastric, pancreatic and liver cancer patients based on minimum caseloads set by the German Cancer Society - Uttinger, Konstantin L.; Diers, Johannes; Baum, Philip; Pietryga, Sebastian; Baumann, Nikolas; Hankir, Mohamed; Germer, Christoph-Thomas; Wiegering, Armin (European journal of surgical oncology, 2022)
Background - The German Cancer Society (DKG) board certifies hospitals in treating esophageal, gastric, liver and pancreatic cancer among others. There has been no systematic verification of the number of major surgical resections set by DKG certification with regards to in-house mortality and failure to rescue (FtR). - Methods - This is a retrospective analysis of anonymized nationwide hospital billing data (DRG data, 2009-2017). Inclusion criteria were based on the annual surgical minimum caseload (SMC) in accordance with DKG certification. - Results - 171,429 datasets were identified, including 31,140 esophageal, 54,155 gastric, 57,343 pancreatic and 28,791 liver resections. In-house mortality ranged from 6.2% for gastric resections to 8.1% for pancreatic resections. Differences in in-house mortality between hospitals which fulfilled SMC on average and those which did not fulfill SMC on average were 40.8% (5.3% vs 8.2%) for esophageal, 32.3% (4.8% vs 6.8%) for gastric and 45.7% (6.1% vs 9.8%) for pancreatic resections, while it was 8.2% higher in SMC-hospitals (7.6% vs 7.0%) for liver resections. Complication occurrence rates for esophageal, gastric and pancreatic resections were similar in SMC- and non-SMC-hospitals while FtR in hospitals fulfilling SMC was significantly lower. Data for liver resections demonstrated the same trends only in a sub-analysis of complex procedures. - Conclusion - This study demonstrates an association between caseload threshold defined by DKG and lower mortality in esophageal, gastric, pancreatic and complex liver surgery. In these resections, FtR was reduced if SMC was fulfilled.
Published online 5 December 2021
Gesehen am 16.02.2022